654. DO PATIENTS WITH "EARLY" ESOPHAGEAL CANCER NEED NEOADJUVANT THERAPY?. (24th September 2022) - Venkataramani, Karthik; Karimundackal, George; Jiwnani, Sabita; Niyogi, Devayani; Tiwari, Virendra Kumar; Pramesh, CS
Abstract: Surgery remains the treatment of choice for early esophageal carcinoma (T1/2&N0). However, the available staging modalities have variable accuracy for T&N stages, with considerable understaging of T3/N+ disease depriving them of neoadjuvant therapy (NAT) which has been shown to improve survival and is the standard of care. As adjuvant therapy is ineffective in esophageal cancers, it is critical to identify factors associated with under staging in early esophageal carcinoma and consider NAT in this subset. We conducted a retrospective analysis of a prospectively maintained database of patients undergoing esophagectomy for esophageal cancer at a tertiary referral cancer center from 2011 to 2019. Patients with T1/2&N0, staged with EUS and PET-CT and undergoing upfront surgery were included in the analysis. Patients who underwent upfront surgery due to limited fitness for systemic therapy, non-invasive disease, non-epithelial histology and endoscopic resections were excluded from analysis. Data with respect to epidemiology, staging, perioperative outcomes and follow up was extracted and analyzed using SPSS 26.0 68/1496 patients (4.5%) who underwent esophagectomy had upfront surgery for T1/2&N0 disease. Squamous cancers (93%) of the middle third were the most common. EUS had an accuracy of 67% & 83% for T&N stage respectively with 10.2% & 17% upstaging to T3 & N+ respectively. 3-year overall survival (OS) of all patients undergoing upfront surgery was 75.2%, of the understaged subset was 48.2%, (95% CI 20%-71%) and patients with T3/N+ disease treated with NAT followed by surgery was 55.7%, (95% CI 52.9%-58.4%). Multivariate analysis showed T2 on EUS, tumor size >3.5cm and SUVmax >3.05 to be predictors of understaging Current staging modalities are associated with 20% upstaging to T3 or N+ disease. T2 tumors with size greater than 3.5cm and SUV>3.05 are frequently associated with understaging and these tumors have poorer outcomes. Patients with these tumor characteristics may benefit from neoadjuvant therapy followed by surgery.